Roles, Actions, and Therapeutic Potential of Specialized Pro-resolving Lipid Mediators for the Treatment of Inflammation in Cystic Fibrosis - Recchiuti, Antonio; Mattoscio, Domenico; Isopi, Elisa (Frontiers in Pharmacology, 2019)
Non resolving inflammation is the main mechanism of morbidity and mortality among patients suffering from cystic fibrosis (CF), the most common life-threatening human genetic disease. Resolution of inflammation is an active process timely controlled by endogenous specialized pro-resolving lipid mediators (SPM) produced locally in inflammatory loci to curtail this innate response, prevent further damages to the host, and permit return to homeostasis. Lipoxins, resolvins, protectins, and maresins are SPM derived from polyunsaturated fatty that limit excessive leukocyte infiltration and pro-inflammatory signals, stimulate innate microbial killing, and enhance resolution Their unique chemical structures, receptors, and bioactions are being elucidated. Accruing data indicate that SPM carry protective functions against unrelenting inflammation and infections in preclinical models and human CF systems. Here, we reviewed their roles and actions in controlling resolution of inflammation, evidence for their impairment in CF, and proofs of principle for their exploitation as innovative, non immunosuppressive, drugs to address inflammation and infections in CF.